(3QhV GdBOGHs - (3GdpqTgGH GrdpMLGRj , CMeO Hf eMeO Hf Ydj GdCfUGQj GdNRQLj, TgGH GdOjf GdeYQha HGdMLGRj,J (B875 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdCOH eWdhH , hGdOGNd ajg eG Hjf eJYhH heYJhH , hbO SCdfi ef dG CSJWjY dg QOkG Gf CLeY dg CTjGA ef GdebGWjY GdOGFaI s
(3BNQgG (B:s
(3hdi Ydjc TQW hgh Gfi EPG LYJ JWYefi eG CTJgi YQjJ JcShfi hGPG YjjJ JMedfi hhai Gddg di HeG GTJQWJg s
(3HGdeYgO fSNI CNQi (B" (3GfXQ ai GdLRA GdChd Qbe (B429 (3COHs
(3HChdgG JYdjbGJ hJejdcGJ CbOegG eDQN (B1106 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B219s
Keywords: (3GdCOHs